The Terraced Slopes of the Douro Valley - Pereira, Susana (2020)
The Douro Valley is widely known because of the oldest demarcated wine region in the world dating from 1756, the Alto Douro Wine Region. The landscape of the Douro Valley was transformed by human activities and reflects the evolution of winemaking for nearly two thousand years. The Alto Douro Wine Region was classified as World Heritage by UNESCO in 2001. Since Romans introduced wine in the Iberian Peninsula in the first century ac, the Douro inhabitants planted vineyards in steep slopes. In these bare slopes, soils were artificially created using manual techniques, crushing Cambrian metamorphic rocks and building terraces supported by schist stone walls, to prevent soil erosion. The Douro Valley presents a temperate climate with a dry and hot summer, which is crucial for vine growth and grapes maturation. Local topographical characteristics, such as elevation, slope and aspect, are important factors affecting the viticulture and oenological characteristics of this specific region. In the Douro Region, slope angle controlled the land management practices, imposing the construction of terraces with schist stone walls. More recently, land embankments have been built in order to create flat surfaces to plant the vines. These structures originated a unique terraced landscape. The geomorphological features of the Douro Valley are described, including specific climatic, geologic, tectonic, soil and anthropogenic aspects that distinguish this region, unique to produce the famous Port wine and UNESCO World Heritage.